2016
DOI: 10.1080/21659087.2016.1142637
|View full text |Cite
|
Sign up to set email alerts
|

Study of the cortical representation of whisker frequency selectivity using voltage-sensitive dye optical imaging

Abstract: The facial whiskers of rodents act as a high-resolution tactile apparatus that allow the animal to detect the finest details of its environment. Previously it was shown that whisker-sensitive neurons in the somatosensory cortex show frequency selectivity to small amplitude stimuli, An intravital voltage-sensitive dye optical imaging (VSDi) method in combination with the different frequency whisker stimulation was used in order to visualize neural activity in the mice somatosensory cortex in response to the sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…Other groups are combining animal experiments with single unit cortical recording and behavioural experiments to understand the neural code for tactile information at higher levels of the nervous system (Harvey et al, 2013). Studies in the barrel cortex of mice, an important tactile area for whisker inputs in rodents, suggests that strong integration of whisker movements occurs over a short time period of less than 25 ms (Stüttgen and Schwarz, 2010;Estebanez et al, 2012;Tsytsarev et al, 2016), which fits well with our observations. Weaker integration of one or two inter-spike intervals over longer time periods has also been reported (Pitas et al, 2016), which supports the importance of temporal pattern encoding, and may underlie the recognition of the burst gap intervals.…”
Section: Using Temporal Neural Codes To Improve Sensory Neural Prosthsupporting
confidence: 86%
“…Other groups are combining animal experiments with single unit cortical recording and behavioural experiments to understand the neural code for tactile information at higher levels of the nervous system (Harvey et al, 2013). Studies in the barrel cortex of mice, an important tactile area for whisker inputs in rodents, suggests that strong integration of whisker movements occurs over a short time period of less than 25 ms (Stüttgen and Schwarz, 2010;Estebanez et al, 2012;Tsytsarev et al, 2016), which fits well with our observations. Weaker integration of one or two inter-spike intervals over longer time periods has also been reported (Pitas et al, 2016), which supports the importance of temporal pattern encoding, and may underlie the recognition of the burst gap intervals.…”
Section: Using Temporal Neural Codes To Improve Sensory Neural Prosthsupporting
confidence: 86%
“…We have investigated the altered bilateral sensory processing produced by CSD using voltage‐sensitive dye (VSD) imaging under somatosensory and cortical surface stimulation (CSS) in mice. VSD imaging can represent neuronal electrical activities at high spatial and temporal resolution , which has previously been applied on the neocortex of mice to reveal the interactions between different pathways during sensory control . We first observed the selective deficits of bilateral sensory‐evoked responses produced by CSD.…”
Section: Introductionsupporting
confidence: 90%
“…By analogy, FA mechanoreceptors of rodents likely have an optimal response around the whisker's resonance frequency (Andermann et al, 2004). Recent Voltage Sensitive Optical Imaging (VSDi) experiments have also shown that the neural activity in the barrel cortex, in response to oscillatory excitation of the whisker was enhanced when the excitation frequency is about 300 Hz (Tsytsarev et al, 2016). Since f w is much lower than f 0 by more than an order of magnitude, one may expect that whisking in air will trigger less activity in FA neurons.…”
Section: Discussionmentioning
confidence: 99%